PENERAPAN MEDIA BONEKA TANGAN BERBANTUAN METODE MAKE A MACTH UNTUK MENINGKATKAN KEMAMPUAN BERCERITA SISWA KELAS II SD STKIP MUHAMMADIYAH BANGKA BELITUNG - Ali Sodikin; Asyraf Suryadin; Sasih Karnita Arafatun (Sekolah Tinggi Pariwisata Mataram, 2020)
The problem of this research was the presence of the students who are shy when telling stories in front of the class, and the student’s lack in involvement during the learning process. From the number of 28 students in a class there are 18 students whose the skills in telling the story are poor. This research was carried out to find out whether there was an increasingof the student’s ability in tellingthe stories on story telling materials in grade II of STKIP Muhammadiyah Elementary School. This research is quantitative type, with the method